Predictors of Poor Seizure Control in Children Managed at a Tertiary Care Hospital of Eastern Nepal - POUDEL, Prakash; CHITLANGIA, Mohit; POKHAREL, Rita (Iranian Journal of Child Neurology, 2016)
How to Cite This Article: Poudel P, Chitlangia M, Pokharel R. Predictors of Poor Seizure Control in Children Managed at a Tertiary Care Hospital of Eastern Nepal Iran J Child Neurol. Summer 2016; 10(3):48-56. Abstract Objective Various factors have been claimed to predict outcome of afebrile seizures in children. This study was aimed to find out the predictors of poor seizure control in children at a resource limited setting. Materials & Methods This prospective study was done from July 1st, 2009 to January 31st, 2012 at B.P. Koirala Institute of Health Sciences, Nepal. Children (1 month-20 yr of age) with afebrile seizures presenting to pediatric neurology clinic were studied. Significant predictors on bivariate analysis were further analyzed with binary logistic model to find out the true predictors. Positive predictive values (PPVs) and negative predictive values (NPVs) for the true predictors were calculated. Results Out of 256 patients (male: female ratio 3:2) with afebrile seizures followed up for median duration of 27 (IQR 12-50) months, seizure was poorly controlled in 20% patients. Three factors predicted poor seizure control. They were frequent (≥1 per month) seizures at onset (OR 12.76, 95% CI 1.44-112.73, PPV 25%, NPV 98%); remote symptomatic etiology (OR 3.56, 95% CI 1.04-12.17, PPV 36%, NPV 92%); and need of more than one anticonvulsant drug (polytherapy) (OR 12.83, 95% CI 5.50-29.9, PPV 56%, NPV 96%). The strongest predictor was need of polytherapy. When all three factors were present, PPV and NPV for prediction of poor seizure control were 70% and 90% respectively. Conclusion Frequent seizures at onset, remote symptomatic etiology of seizure and need of polytherapy were associated with poor seizure control in children with afebrile seizures. References Sander JW, Shorvon SD. Epidemiology of the epilepsies. J Neurol Neurosurg Psychiatry 1996; 61:433-43. Johnston MV. Seizures in Childhood. In: Behman RE, Kleigman RM, Jenson HB, eds. Nelson Textbook of Pediatrics 17thed. Philadelphia: Saunders, 2004:1993-2005. Sillanpaa M. Remission of seizures and prediction of intractability in long-term follow-up. Epilepsia 1993; 34:930-6. Harrison RM, Taylor DC. Childhood seizures: a 25-year follow-up, social and medical prognosis. Lancet 1976; 1:948-51. Berg AT, Levy SR, Novotny EJ, Shinnar S. Predictors of intractable epilepsy in childhood: a case-control study. Epilepsia 1996; 37:24-30. Malik MA, Hamid MH, Ahmed TM, Ali Q. Predictors of intractable childhood epilepsy. J Coll Physicians Surg Pak 2008; 18:158-62. Kwong KL, Sung WY, Wong SN, So KT. Early predictors of medical intractability in childhood epilepsy. Pediatr Neurol 2003; 29:46-52. Chawla S, Aneja S, Kashyap R, Mallika V. Etiology and clinical predictors ofintractable epilepsy. Pediatr Neurol 2002; 27:186-91. Shinnar S, Berg AT, Moshe SL, O’Dell C, Alemany M, Newstein D et al. The risk of seizure recurrence after a first unprovoked afebrile seizure in childhood: an extended follow-up. Pediatrics 1996; 98:216-25. Shinnar S, Berg AT, Moshé SL, Petix M, Maytal J, Kang H et al. Risk of seizure recurrence following a first unprovoked seizure in childhood: a prospective study. Pediatrics 1990;85:1076-85. Sillanpää M, Schmidt D. Early seizure frequency and aetiology predict long-term medical outcome in childhood-onset epilepsy. Brain 2009; 132:989-98. Casetta I, Granieri E, Monetti VC, Gilli G, Tola MR, Paolino E et al. Early predictors of intractability in childhood epilepsy: a community-based case-control study in Copparo, Italy. Acta Neurol Scand 1999; 99:329-33. Stroink H, Brouwer OF, Arts WF, Geerts AT, Peters AC, van Donselaar CA. The first unprovoked, untreated seizure in childhood: a hospital based study of the accuracy of the diagnosis, rate of recurrence, and long term outcome after recurrence. Dutch study of epilepsy in childhood. J Neurol Neurosurg Psychiatry 1998; 64:595-600. Tripathi M, Padhy UP, Vibha D, Bhatia R, Padma Srivastava MV, Singh MB et al. Predictors of refractory epilepsy in north India: a case-control study. Seizure 2011; 20:779-83. Oskoui M, Webster RI, Zhang X, Shevell MI. Factors predictive of outcome in childhood epilepsy. J Child Neurol 2005; 20:898-904. Lohani S, Devkota UP, Rajbhandari H. Predictors of unfavourable seizure outcome in patients with epilepsy in Nepal. Can J Neurol Sci 2010; 37:76-80. Beume LA, Steinhoff BJ. Long-term outcome of difficult-to treat epilepsy in childhood. Neuropediatrics 2010; 41:135-9. Bouma PA, Peters AC, Brouwer OF. Long term course of childhood epilepsy following relapse after antiepileptic drug withdrawal. J Neurol Neurosurg Psychiatry 2002; 72:507-10. Commission on Classification and Terminology of the International League Against Epilepsy. Proposal for revised clinical and electroencephalographic classification of epileptic seizures. Epilepsia 1981; 22:489-501. Kwan P, Brodie MJ. Effectiveness of first antiepileptic drug. Epilepsia 2001; 42:1255-60. Dörks M, Langner I, Timmer A, Garbe E. Treatment of pediatric epilepsy in Germany: Antiepileptic drug utilization in children and adolescents with a focus on new antiepileptic drugs. Epilepsy Res 2013;103:45-53 Herman ST. Single Unprovoked Seizures. Curr Treat Options Neurol 2004; 6:243-55. Boonluksiri P. Risk of recurrence following a first unprovoked seizure in Thai children. Neurol J Southeast Asia 2003; 8:25-9. Parra J, Augustijn PB, Greets Y, van Emde Boas W. Classification of Epileptic Seizures: A Comparison of Two Systems. Epilepsia 2001; 42:476-82. Eeg-Olofsson O. The development of the electroencephalogram in normal children and adolescents from the age of 1 through 21 years. Acta Paediatr Scand 1971; Suppl 208:1-46.